Kinetics and Mechanism of Oxidation of Aliphatic and Aromatic Suphoxides by Peroxomonosulphate - Janakiram, T.; Maruthamuthu, P.; Krishna Pillay, M. (Asian Journal of Chemistry, 2010)
The title reaction in aqueous acetic acid shows first order dependence each on [oxidant] and [substrate]. Changes in [H+] and ionic strength have no effect on the reaction rate. The kinetic and thermodynamic parameters have been evaluated and a suitable mechanism proposed.